2017
DOI: 10.1210/en.2017-00630
|View full text |Cite
|
Sign up to set email alerts
|

Selective Pharmacogenetic Activation of Catecholamine Subgroups in the Ventrolateral Medulla Elicits Key Glucoregulatory Responses

Abstract: Catecholamine (CA) neurons in the ventrolateral medulla (VLM) contribute importantly to glucoregulation during glucose deficit. However, it is not known which CA neurons elicit different glucoregulatory responses or whether selective activation of CA neurons is sufficient to elicit these responses. Therefore, to selectively activate CA subpopulations, we injected male or female Th-Cre+ transgenic rats with the Cre-dependent DREADD construct, AAV2-DIO-hSyn-hM3D(Gq)-mCherry, at one of four rostrocaudal levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 62 publications
6
43
0
1
Order By: Relevance
“…Catecholaminergic neurons in the VLM are a key component of the central counterregulatory circuit and the ability of these neurons to evoke hyperglycaemia (Ritter et al, 2000;Zhao et al, 2017;Li et al, 2018) and hyperglucagonaemia (Andrew et al, 2007) is well-established. Recent studies have clearly demonstrated that spinally-projecting C1 neurons evoke hyperglycaemia by stimulating the adrenal medulla (Zhao et al, 2017;Li et al, 2018), suggesting that the response is likely to be mediated by corticosterone and/or adrenaline. We also show that activation of A1/C1 neurons evokes hyperglycaemia, but by promoting glucagon release.…”
Section: A1/c1 Neurons Mediate the Avp Response To Insulin-induced Hymentioning
confidence: 99%
See 1 more Smart Citation
“…Catecholaminergic neurons in the VLM are a key component of the central counterregulatory circuit and the ability of these neurons to evoke hyperglycaemia (Ritter et al, 2000;Zhao et al, 2017;Li et al, 2018) and hyperglucagonaemia (Andrew et al, 2007) is well-established. Recent studies have clearly demonstrated that spinally-projecting C1 neurons evoke hyperglycaemia by stimulating the adrenal medulla (Zhao et al, 2017;Li et al, 2018), suggesting that the response is likely to be mediated by corticosterone and/or adrenaline. We also show that activation of A1/C1 neurons evokes hyperglycaemia, but by promoting glucagon release.…”
Section: A1/c1 Neurons Mediate the Avp Response To Insulin-induced Hymentioning
confidence: 99%
“…Many physiological stressors activate hindbrain catecholamine neurons, which release noradrenaline (A1) or adrenaline (C1) and reside in the ventrolateral portion of the medulla oblongata (VLM). Activation of C1 neurons (by targeted glucoprivation or chemogenetic manipulation) is known to elevate blood glucose (Ritter et al, 2000;Zhao et al, 2017;Li et al, 2018) and plasma glucagon (Andrew et al, 2007). Furthermore, C1 cell lesions severely attenuate the release of AVP in response to hydralazine-evoked hypotension (Madden et al, 2006), indicating that this hindbrain site may be a key regulator of AVP neuron activity during physiological stress.…”
Section: Hypoglycaemia Evokes Avp Secretion Via Activation Of A1/c1 Nmentioning
confidence: 99%
“…Future studies could also help determine whether these measures are correlated with PV expression. Although this matter was beyond the scope of this study, based on previous studies (Wirtshafter and Stratford, 2016;Li et al, 2018;Cisneros-Franco and de Villers-Sidani, 2019), a correspondence between the specific chemogenetic manipulation and PV staining intensity is to be expected. In addition, future studies are needed to determine whether the role of PV-related inhibition on auditory discrimination abilities is lateralized.…”
Section: Discussionmentioning
confidence: 83%
“…Following dura removal with a 27-G needle, 1 μL virus (pAAV-hSYN-DIO-hM4D(Gi)-mCherry or pAAV-hSYN-DIO-hM3D(Gq)-mCherry was injected using a precision syringe pump (PHD Ultra 4400, Harvard Apparatus, Holliston, MA) at a rate of 0.05 μL/min. The surgical wound was sutured and cleaned, the rat was monitored until full recovery and medicated with antibiotic (enrofloxacin, 10 mg/kg, s.c.) and analgesic (carprofen, 5 mg/kg, s.c.) for at least 3 days (Wirtshafter and Stratford, 2016;Li et al, 2018).…”
Section: Stereotaxic Injectionsmentioning
confidence: 99%
“…Glucose sensors in the hindbrain and PMV are critical for the CRR as detailed in several comprehensive review articles (Ritter et al, 2011 ; Routh et al, 2012 ; Donovan and Watts, 2014 ). Ritter and colleagues show that specific clusters of catecholamine neurons within the C1 cell groups (C1r, C1m, A1/C1) of the rostral ventral lateral medulla (RVLM) in rodents are essential for individual components of hypoglycemia correction including epinephrine and corticosterone secretion as well as glucoprivic feeding (Ritter et al, 1981 , 1998 , 2001 , 2006 ; Li et al, 2017 ). The feeding and corticosterone response is mediated by forebrain projections to hypothalamus (i.e.…”
Section: Relationship Between Hypothalamic Hindbrain and Portal-mesementioning
confidence: 99%